Beneficial Cardiac Structural and Functional Adaptations After Lumbosacral Spinal Cord Epidural Stimulation and Task-Specific Interventions: A Pilot Study - Legg Ditterline, Bonnie E.; Wade, Shelley; Ugiliweneza, Beatrice; Singam, Narayana Sarma; Harkema, Susan J.; Stoddard, Marcus F.; Hirsch, Glenn A. (Frontiers in Neuroscience, 2020)
Cardiac myocyte atrophy and the resulting decreases to the left ventricular mass and dimensions are well documented in spinal cord injury. Therapeutic interventions that increase preload can increase the chamber size and improve the diastolic filling ratios; however, there are no data describing cardiac adaptation to chronic afterload increases. Research from our center has demonstrated that spinal cord epidural stimulation (scES) can normalize arterial blood pressure, so we decided to investigate the effects of scES on cardiac function using echocardiography. Four individuals with chronic, motor-complete cervical spinal cord injury were implanted with a stimulator over the lumbosacral enlargement. We assessed the cardiac structure and function at the following time points: (a) prior to implantation; (b) after scES targeted to increase systolic blood pressure; (c) after the addition of scES targeted to facilitate voluntary (i.e., with intent) movement of the trunk and lower extremities; and (d) after the addition of scES targeted to facilitate independent, overground standing. We found significant improvements to the cardiac structure (left ventricular mass = 10 ± 2 g, p < 0.001; internal dimension during diastole = 0.1 ± 0.04 cm, p < 0.05; internal dimension during systole = 0.06 ± 0.03 cm, p < 0.05; interventricular septum dimension = 0.04 ± 0.02 cm, p < 0.05), systolic function (ejection fraction = 1 ± 0.4%, p < 0.05; velocity time integral = 2 ± 0.4 cm, p < 0.001; stroke volume = 4.4 ± 1.5 ml, p < 0.01), and diastolic function (mitral valve deceleration time = -32 ± 11 ms, p < 0.05; mitral valve deceleration slope = 50 ± 25 cm s–1, p < 0.05; isovolumic relaxation time = −6 ± 1.9 ms, p < 0.05) with each subsequent scES intervention. Despite the pilot nature of this study, statistically significant improvements to the cardiac structure, systolic function, and diastolic function demonstrate that scES combined with task-specific interventions led to beneficial cardiac remodeling, which can reverse atrophic changes that result from spinal cord injury. Long-term improvements to cardiac function have implications for increased quality of life and improved cardiovascular health in individuals with spinal cord injury, decreasing the risk of cardiovascular morbidity and mortality.